Breastfeeding Practices and Problems Among Obese Women Compared with Nonobese Women in a Brazilian Hospital - Marina Rico Perez; Luc?ola Sant'Anna de Castro; Yan-Shing Chang; Adriana Sa?udo; Karla Oliveira Marcacine; Lisa H Amir; Michael G. Ross; Kelly Pereira Coca (Mary Ann Liebert, 2021)
Background: Women who are obese have lower rates of breastfeeding initiation and duration and are less likely to breastfeed exclusively compared with women who are not obese. To develop programs to improve breastfeeding practices among this group of women, we investigated the association between maternal obesity and breastfeeding practices and problems in the first days postpartum. Methods: We analyzed medical records from postpartum women at a rooming-in maternity ward in State of S?o Paulo, Brazil, between 2016 and 2018. We included those who had intended to exclusively breastfeed, had given birth to a singleton and were admitted to rooming-in. We analyzed exclusive breastfeeding and nonexclusive breastfeeding each day of hospitalization and the presence of breastfeeding problems, comparing women in the obese category (body mass index [BMI] ?30?kg/m2) to normal and overweight women (?18.6 to ?29.9?kg/m2). Results: Two hundred and twenty-four postpartum women participated, including 86 women in the obese category. More than 50% of women with obesity reported a breastfeeding problem in the first and second postpartum days (p?=?0.026 and p?=?0.017, respectively) compared with the 41% and 38% nonobese group. Children of obese women were 2.8 times more likely to have poor latch during breastfeeding (95% confidence interval [CI]: 1.29?6.10) compared with the nonobese group on the third day. Conclusion: Maternal obesity increased the probability of breastfeeding difficulties and nonexclusive breastfeeding at discharge. Professionals need to support breastfeeding techniques in the days immediate after delivery to improve breastfeeding outcomes for mothers with obesity.